Rekrutmen dan Seleksi SDM Berbasis Nilai Pendidikan Islam: Strategi Efektif untuk Peningkatan Mutu Lembaga Pendidikan - Sa'diyah Handayani; Wahyu Septiani; M. Ajib Hermawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the concept and process of human resource (HR) recruitment and selection in Islamic educational institutions, identify effective strategies such as needs planning and the use of digital media, and their application based on Islamic values, including Al-Qur'an memorization tests and moral character evaluation to improve the quality of education holistically. The research method used a descriptive qualitative approach through a literature study of 15 scientific journal references and HR management books from 2021-2025, with in-depth content analysis and source triangulation to ensure the validity and reliability of the findings. The results show that recruitment and selection involve stages of HR planning, widespread vacancy announcements, and multi-layered selection such as administration, written competency tests, in-depth interviews, and microteaching, supported by transparent strategies through school websites, social media, and multidisciplinary teams to reduce subjectivity. The discussion highlights key challenges in Indonesia, such as a lack of transparency in the recruitment process, uneven distribution of teachers in remote areas, and adaptation to educational technology, which can be overcome through a holistic approach combining professional competence, moral integrity, and Islamic character so that teachers are not only intellectually intelligent but also role models of noble character for students. The conclusion states that the recruitment-selection process is fundamental to producing high-quality and sustainable educational human resources, with recommendations for developing a competency-based digital system, recruiter training, and periodic evaluation of teacher performance after recruitment in Islamic educational institutions.